The Latin American Social Medicine database - Wiley Kevin; Iriart Celia; Teal Janis; Buchanan Holly S; Waitzkin Howard; Eldredge Jonathan D; Tregear Jonathan (BMC, 2004)
Abstract Background Public health practitioners and researchers for many years have been attempting to understand more clearly the links between social conditions and the health of populations. Until recently, most public health professionals in English-speaking countries were unaware that their colleagues in Latin America had developed an entire field of inquiry and practice devoted to making these links more clearly understood. The Latin American Social Medicine (LASM) database finally bridges this previous gap. Description This public health informatics case study describes the key features of a unique information resource intended to improve access to LASM literature and to augment understanding about the social determinants of health. This case study includes both quantitative and qualitative evaluation data. Currently the LASM database at The University of New Mexico http://hsc.unm.edu/lasm brings important information, originally known mostly within professional networks located in Latin American countries to public health professionals worldwide via the Internet. The LASM database uses Spanish, Portuguese, and English language trilingual, structured abstracts to summarize classic and contemporary works. Conclusion This database provides helpful information for public health professionals on the social determinants of health and expands access to LASM.